HUBUNGAN RIWAYAT STATUS GIZI IBU SAAT HAMIL DENGAN KEJADIAN STUNTING PADA ANAK BALITA - Juwita, Ratna; Fentia, Lia; Lestari, Rahmadhani Fuji; Zalni, Rummy Islami (Ensiklopedia of Journal, 2024)
Stunting is a condition of growth failure in children under five due to chronic malnutrition, especially in the first 1,000 days of life. In Dumai City, the highest prevalence of stunting is in Purnama Village with 62 stunted toddlers (38.9%) out of a total of 159 toddlers. One of the factors causing stunting in children under five is the nutritional condition of the mother during pregnancy. In the city of Dumai, there are 315 pregnant women with chronic energy deficiency. This study aims to determine the relationship between the history of maternal nutritional status during pregnancy and the incidence of stunting in children under five years of age. The study used an analytic method with a cross sectional approach. The population in this study were mothers who had toddlers with a sample size of 96 respondents. The results showed that 41% were stunted. The statistical test results show that there is a significant relationship between the size of the mother's LILA during pregnancy (p value 0.008), history of anemia during pregnancy (p value 0.020), body mass index of pregnant women (p value 0.036) with the incidence of stunting in children under five. It is expected that respondents, especially mothers, can prepare for a healthy pregnancy by checking themselves to health services before and during pregnancy, to prevent nutritional problems during pregnancy such as chronic energy deficiency, anemia, underweight and other health problems that can increase the risk of stunting in toddlers. Keywords: Stunting; Nutrition; Pregnant Women